A rede internacional de Festivais e a atuação do Festival do Rio: a circulação do longa metragem nacional vencedor do Troféu Redentor de Melhor Filme (2006-2019) - Costa, Nadia Cristina Biondo da (Universidade Federal de São Carlos, 2021)
In Brazil, film festivals have been spaces for the circulation of films for at least fifty years. At the same time that they appear relatively autonomous to other national film circulation windows, they also constitute strategic distribution spaces. As a result, festivals are granted the attribution of a showcase, a primary window. But how does the showcase work? What are the elements and characteristics that make festivals effective and responsible for this attribution? Based on the assumption that festivals operate in a network logic this work seeks to understand the position that Rio Festival occupies within this network and how does this position interfere with the functions assigned to the festival and the works that circulate on the network? To do so, the research surveys the last fourteen feature films (2006-2019) awarded with “Best Film” by the program called Première Brasil. Thus, it was possible to notice a relationship between the festival and other events within the international network of festivals, through elements of validation, selections, premieres and other awards. This work is based on the hypothesis that the festival’s network can work with an end in itself, even if they carry a transnational characteristic that goes beyond their apparent boundaries of action.
The international network of festivals and the performance of the Rio Festival: the circulation of the national feature film winner of the Redentor Trophy for Best Film (2006-2019)
Keywords: Circulação; Rede; Festival de Cinema; Distribuição; Film circulation; Network; Film Festivals; Distribuition; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::ADMINISTRACAO E PRODUCAO DE FILMES